RARE METAL ORE FORMATION OF UKRAINIAN SHIELD - GALETSKY, L.; KIRICHENKO, S.; KOLOSOVSKA, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Ukraine is well known rare metal region, and its main Precambrian structure – the Ukrainian shield is powerful rare metal provinces in the world. Metallogenic analysis on rare metal within the Ukrainian Shield and the map of rare metal within the Ukrainian shield" were realized. There are 22 rare metal ore formations which are include deposits of beryllium, zirconium, rare earth, lithium, niobium, tantalum, scandium and other metals.